Perbedaan Lama Waktu Pengukusan Pada Proses Pemindangan Terhadap Karakteristik Kimia Dan Penerimaan Konsumen Pindang Ikan Bandeng (Chanos chanos) - Burhanuddin, Burhanuddin; Irawan, Irman; Diachanty, Seftylia; Sulistiawati, Septiana; Zuraida, Ita (Jambura Fish Processing Journal, 2026)
Milkfish (Chanos chanos) is one of the leading fishery commodities in East Kalimantan, characterized by its high protein and fat content. One of the efforts to prevent quality degradation in milkfish is through the “pindang” processing method; however, the traditional boiling technique often results in a shorter shelf life. This study aims to evaluate the effect of different steaming durations in the milkfish “pindang” process on chemical characteristics (moisture, ash, fat, and protein content) and consumer preference (hedonic test). The research utilized a Completely Randomized Design (CRD) consisting of four steaming duration treatments: 25 minutes (KP1), 30 minutes (KP2), 35 minutes (KP3), and 40 minutes (KP4), with each treatment replicated three times. Chemical characteristic data were analyzed using Analysis of Variance (ANOVA) at a 95% confidence level, followed by Duncan’s Multiple Range Test (DMRT) if significant effects were found. Meanwhile, hedonic data were analyzed using the Kruskal-Wallis non-parametric test, with the Mann-Whitney test as a post-hoc analysis if significant differences were detected. The results showed that steaming duration significantly affected (p0.05) the chemical characteristics but had no significant effect (p0.05) on the organoleptic parameters (color, aroma, taste, and texture). The chemical characteristics of the product included moisture content (45.59% - 48.81%), ash (1.01% - 1.24%), fat (2.18% - 2.62%), and protein (22.78% - 23.96%). Treatment KP2 (30-minute steaming) was determined as the best treatment based on the optimal balance of nutritional value (23.35% protein and 2.45% fat) and the highest average score in the color sensory parameter (5.40/slightly like).